Upregulation of FGFR3 and HIF-1α expression in muscle invasive bladder cancer (Medical Journal of Indonesia, 2019)
BACKGROUND The major risks in patients diagnosed with non-muscle invasive bladder cancer (NMIBC)are recurrence, progression of muscle invasive bladder cancer (MIBC), and metastasis. Biological markers such as fibroblast growth factor receptor-3 (FGFR3) and hypoxia-inducible factor-1α (HIF-1α) are related to muscle invasiveness of bladder cancer. This study was aimed to analyze the expression of FGFR3 and HIF-1α to predict muscle invasiveness in bladder cancer patients. METHODS This was an observational study with a case-control design. Sixty patients with bladder cancer, who underwent histopathology examinations at the Department of Pathology, Faculty of Medicine, Universitas Sumatera Utara/H. Adam Malik Hospital from January 2012 to December 2015, were included in this study. Samples were then classified into 30 NMIBC and 30 MIBC groups. All samples were analyzed with an immunohistochemistry assay for FGFR3 and HIF-1α. H-scores were used to determine the relationships between each group. RESULTS FGFR3 was expressed in 29 (96.7%) patients of the NMIBC group, and 23 (76.7%) patients of the MIBC group (p=0.026, OR=8.8; 95% CI=1.01–76.96). HIF-1α was expressed in only 1 (3.33%) patient of the NMIBC group, and 15 (50%) patients of the MIBC group (p<0.001, OR=29; 95% CI=3.49–241.13). CONCLUSIONS There was a difference in upregulation of FGFR3 and HIF-1α expression in both the NMIBC and MIBC groups.